2019
DOI: 10.1016/j.celrep.2019.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor NR2F6 Suppresses T Follicular Helper Cell Accumulation through Regulation of IL-21

Abstract: SummaryCD4 T follicular helper (Tfh) cells are specialized in helping B cells during the germinal center (GC) reaction and ultimately promote long-term humoral immunity. Here we report that loss of the nuclear orphan receptor NR2F6 causes enhanced survival and accumulation of Tfh cells, GC B cells, and plasma cells (PCs) following T cell-dependent immunization. Nr2f6-deficient CD4 T cell dysfunction is the primary cause of cell accumulation. Cytokine expression in Nr2f6-deficient Tfh cells is dysregulated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…Additionally, NRs have been shown to regulate the inflammatory process, which is an important component in the development of NAFLD/NASH and insulin resistance. Given that NR2F6 is a critical regulator of immune response and cytokine production, [ 32,33 ] we speculate that the role of NR2F6 in the hepatic inflammation and lipid metabolism might be partially interdependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NRs have been shown to regulate the inflammatory process, which is an important component in the development of NAFLD/NASH and insulin resistance. Given that NR2F6 is a critical regulator of immune response and cytokine production, [ 32,33 ] we speculate that the role of NR2F6 in the hepatic inflammation and lipid metabolism might be partially interdependent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the NR2F-specific binding oligonucleotide sequence contains a TGACCT motif. [32,33] We analyzed the promoter region of mouse CD36 gene (−2000 bp from the transcriptional start site) and found a potential NR2F6 binding site at −1916 bp ( Figure 3G). It is of interest that this binding site also exists in the promoter region of human CD36 gene (Figure 3G).…”
Section: Nr2f6 Promotes Cd36 Expression Through Directly Binding To Tmentioning
confidence: 99%
“…Memory CD8 + T-cell precursors form early in the antibacterial effector phase and can be characterized by effector functions, tissue localization, and cell surface determined [14][15][16][17][18] . Using germ-line knockout mice, we have identified functions of the orphan NR, NR2F6 in effector CD4 + and CD8 + T-lymphocytes during cancer progression, autoimmune responses, and immunization [19][20][21][22][23][24] . Mechanistically, NR2F6 suppresses the transcription of cytokine genes directly (Il21) or via blocking the binding of activating transcription factors such as NFAT/AP-1 to the promoter and/or other conserved regulatory sequences (Il2, Ifng, Il17), thus acting as a brake on inflammatory cytokine responses 19,20,22,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Using germ-line knockout mice, we have identified functions of the orphan NR, NR2F6 in effector CD4 + and CD8 + T-lymphocytes during cancer progression, autoimmune responses, and immunization [19][20][21][22][23][24] . Mechanistically, NR2F6 suppresses the transcription of cytokine genes directly (Il21) or via blocking the binding of activating transcription factors such as NFAT/AP-1 to the promoter and/or other conserved regulatory sequences (Il2, Ifng, Il17), thus acting as a brake on inflammatory cytokine responses 19,20,22,24 . Our previous tumor experiments demonstrated that Nr2f6-deficient mice have superior protective memory responses 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also known for its functions as a transcription factor, coactivator, and repressor for the expression of various genes, including hormones, hormone receptors, and apolipoproteins [ 12 , 13 , 14 , 15 , 16 , 17 ]. In immune cells, it helps to regulate the expression of cytokines like Interleukin-21 (IL-21) or Interferon-γ (IFN-γ) [ 18 , 19 ], and it is also a negative regulator of T-cell development [ 20 ]. NR2F6 was defined as an intracellular immune checkpoint in tumor-infiltrating T-cells.…”
Section: Introductionmentioning
confidence: 99%